Measurements of Drag Torque, Lift-Off Journal Speed, and Temperature in a Metal Mesh Foil Bearing - Andres, Luis-San; Chirathadam, Thomas Abraham; Ryu, Keun; Kim, Tae Ho (ASME, 2010)
Metal mesh foil bearings (MMFBs) are a promising low cost gas bearing technology for high performance oil-free microturbomachinery. Elimination of complex oil lubrication and sealing system by deploying MMFBs in rotorcraft gas turbine engines offers distinctive advantages such as reduced system weight, enhanced reliability at high rotational speeds and extreme temperatures, and extended maintenance intervals compared with mineral oil lubricated bearings. MMFBs for oil-free rotorcraft engines must demonstrate adequate load capacity, reliable rotordynamic performance, and low frictional losses in a high temperature environment. The paper presents the measurements of MMFB breakaway torque, rotor lift-off and touchdown. speeds, and temperature at increasing static load conditions. The tests, which were conducted in a test rig driven by an automotive turbocharger turbine, demonstrate the airborne operation (hydrodynamic gas film) of the floating test MMFB with little frictional loses at increasing loads. The measured drag torque peaks when the rotor starts and stops, and drops significantly once the bearing lifts off The estimated rotor speed for lift-off increases linearly with the applied static load. During continuous operation, the MMFB temperature measured at the back surface of the top foil increases both with rotor speed and static load. Nonetheless, the temperature rise is mild, demonstrating reliable performance. Application of a sacrificial layer of solid lubricant on the top foil surface reduces the rotor break-away torque. The measurements give confidence on this simple bearing technology for ready application into oil-free turbomachinery. [DOI: 10.1115/1.4000863]